Involvement of the GABA-Ergic System in Anxiolytic- and Antidepressive Effects of the Scrophularia striata Extract in Rats - Babri, Sh.; Kosari-Nasab, M.; Fatehi-Gharehlar, L.; Doosti, M.H. (Нейрофизиология, 2013)
Recently, neuroprotective and anti-inflammatory effects of an extract of Scrophularia striata Boiss (Sc. st.) (Scrophulariaceae) were shown in rodents. In our study, we investigated the effects of the Sc. st. extract on anxiety and depression-like behaviors in rats and tried to find possible mechanisms responsible for these influences. The elevated plus-maze (EPM) and forced swimming test (FST) were used. The ethanol extract of Sc. st. was perorally administered at different doses (20, 50, 100, 160, and 220 mg/kg). We also assessed interaction between the effective doses of Sc. st. and GABAA receptors in the brain. It was found that Sc. st. at doses of 100 and 160 mg/kg increased normalized values of the open arm time and number of entries in the EPM and decreased the immobility time in the FST in comparison with the control group, indicating anxiolytic and antidepression effects, respectively. Intracerebroventricular administrations of a GABAA receptor agonist, muscimol (0.5, 0.75, and 1 µg/rat), enhanced the respective Sc. st. effects, while a GABAA receptor antagonist, bicuculline (0.5, 1 and 2 µg/rat), blocked these effects. Thus, anxiolytic and antidepressive effects of the active components of Sc. st. may be mediated by modulation of the GABAergic system. Нещодавно в експериментах на гризунах були продемонстровані нейропротективні та протизапальні ефекти екстракту ранника смугастого, Scrophularia striata Boiss (Sc. st., Scrophulariaceae). Ми досліджували впливи екстракту Sc. st. на аспекти поведінки щурів, пов’язані з тривожністю та депресивністю, і намагалися з’ясувати механізми, відповідальні за реалізацію цих впливів. Тестували поведінку в піднятому лабіринті (ПЛ) і в тесті вимушеного плавання (ТВП). 20, 50, 100, 160 або 220 мг/кг сухої речовини спиртового екстракту Sc. st. уводилися перорально у вигляді водного розчину. Ми також досліджували взаємодію екстракту Sc. st. в ефективних дозах і ГАМКА-рецепторів у головному мозку. Екстракт у дозах 100 та 160 мг/кг забезпечував вірогідне збільшення нормованих значень часу перебування у відкритій гілці ПЛ і числа входів до неї і зменшував тривалість періоду нерухомості в ТВП порівняно з відповідними значеннями в контрольній групі; це свідчило, відповідно, про анксіолітичний та антидепресивний ефекти. Внутрішньошлуночкові введення агоніста ГАМКA-рецепторів мусцимолу (0.5, 0.75 і 1 мкг на тварину) посилювали відповідні ефекти Sc. st. Антагоніст же ГАМКA-рецепторів бікукулін (0.5, 1 і 2 мкг на щура) блокував ці ефекти. Таким чином, анксіолітичні та антидепресивні ефекти активних компонентів Sc. st. можуть опосередковуватися модуляцією стану ГАМК-ергічної системи.